Założenia do projektu scalenia gruntów jako instrument kształtowania rolniczych zasobów wodnych = Assumptions for land consolidation project as an instrument for forming agricultural water resources - Pijanowski, Jacek M.; Posiak, Barbara (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
An important element of the assumptions for the land consolidation project are studies covering the sphere of agricultural water resources management, including land reclamation and retention - very valid in the face of growing threats in our country related to spates and floods but also to drought. The research aims to present the results of the assumptions for the land consolidation project as an instrument for shaping agricultural water resources on the example of model research and implementation works carried out by the Lesser Poland Voivodeship in cooperation with the Federal State of Thuringia.
Keywords: założenia do projektu scalenia gruntów; scalanie gruntów; rolnicze zasoby wodne; assumptions for the land consolidation project; land consolidation; agricultural water resources